Artificial Intelligence, Big Data, Automation, MBTI, and HR Performance in the Digital Era - Hakim, Chairul; Yansen, Albert; Hernaningsih, Fery; Alifia, Firda Hafidh; Zidni, Irfan (Universitas Batanghari Jambi, 2025)
Business Landscape Transformation and Its Impact on Human Resource Management in the Digital Era. The business landscape, which has undergone a fundamental transformation due to the digital era, presents new opportunities and challenges in human resource (HR) management. In the increasingly digital corporate world, this study will explore the impact of automation, big data, artificial intelligence (AI), and MBTI on HR effectiveness. The aim of this research is to understand the influence of these technologies on HR, both positively and negatively.The research methodology involves surveys, data analysis, and case studies on small and medium-sized enterprises (SMEs). One of the issues discussed is the extent to which AI has changed the way HR carries out daily tasks. AI has the potential to significantly impact HR by helping companies improve recruitment procedures, offer specialized training, and anticipate future workforce needs. Additionally, this study will examine how big data has emerged as a useful tool in HR decision-making. The accuracy of MBTI, derived from various sources, will provide a comprehensive understanding of employee performance, job satisfaction, and productivity patterns. Furthermore, automation will be analyzed to assess how much mundane workplace tasks can be replaced by technology, thereby allowing HR staff to focus on more strategic and impactful work for the company